Rat Brown Adipose Tissue Uncoupling Protein: Identification of Potential Targeting Sequence(s) - Reichling, Susanna (My University, 1990)
Uncoupling protein, a mitochondrial inner membrane protein found in mammalian brown adipose tissue, functions as an uncoupler of oxidative phosphorylation by serving as a proton carrier when activated, resulting in heat production, the function of the tissue. Unlike most nuclear-encoded mitochondrial proteins, uncoupling protein is not made with a cleavable presequence. With the availability of an uncoupling protein cDNA clone, the region responsible for targeting uncoupling protein to mitochondria was examined using in vitro transcription and translation and import into isolated mitochondria. In order to localize the targeting sequence of uncoupling protein, fusion proteins containing portions of uncoupling protein and uncoupling protein modified by site-directed mutagenesis were constructed and analysed for their ability to be imported. Previously it has been shown that there was a targeting signal within uncoupling protein amino acids 13 to 105 (Liu et al., 1988). However, amino acids 13 to 51 did not target a passenger protein to mitochondria (Liu et al., 1988). Here the role of amino acids 53 to 105 of uncoupling protein in targeting was examined with two new constructs, uncoupling protein amino acids 53 to 105 joined to rat ornithine carbamoyltransferase amino acids 147 to 354 and to mouse dihydrofolate reductase. These two constructs along with uncoupling protein with amino acids 2 to 51 deleted were imported into mitochondria consistent with uncoupling protein amino acids 53 to 105 having a potential targeting role in uncoupling protein. Further, these three constructs were processed upon import. The major processed forms of all three constructs are approximately 20 amino acids smaller than the initial translation product. Both fusion constructs also have an intermediate-sized processed form approximately 14 amino acids smaller than the initial translation product. Processing suggests that at least the amino terminus of these proteins has reached the mitochondrial matrix. The location of the proteins was examined using Na2CO3 extraction. Uncoupling protein and U13-105-OCT (uncoupling protein amino acids 13 to 105 joined to ornithine carbamoyltransferase amino acids 147 to 354) were found in the membrane fraction while the processed forms of Ud2-51 (uncoupling protein with amino acids 2 to 52 deleted) and U53-105-DHFR (uncoupling protein amino acids 53 to 105 joined to dihydrofolate reductase) were found in the aqueous fraction suggesting that uncoupling protein amino acids 2 to 52/53 are involved in membrane localization. Analysis of Ud2-35 (uncoupling protein with amino acids 2 to 35 deleted) revealed that it was associated with both the membrane and aqueous fractions. Analysis of uncoupling protein amino acids 53 to 105 revealed the potential existence of two positively charged amphipathic a-helices. Based on the sizes of processed forms and on the helical wheel projection for the first possible sequence, arginine54 , lysine56 and lysine67 were changed to glutamines, individually and in various combinations using oligonucleotide site-directed mutagenesis. All mutant proteins were imported into mitochondria even when all three basic amino acids were replaced. The results suggest that this portion of uncoupling protein, amino acids 54 to 67, is not a targeting signal in the protein.
Targeting Sequences of Rat Uncoupling Protein
Keywords: adipose tissue; uncoupling protein; targeting se quence; rat brown